CIDI 20 years - Perspectives on Information Design - Smythe, Kelli C.A.S.; C. Andrade, Rafael (InfoDesign, 2023)
Celebrating the 20th anniversary of the Information Design International Conference, this special issue of Infodesign presents a selection of evaluated papers at CIDI 2023. The selected works present different aspects of Information Design in contemporary research performed in Brazil and in countries such as Ireland, England, Belgium, Portugal, the United States, Canada and Chile. Theory and practice are mixed in methodological, historical and educational perspectives, demonstrating the plurality of the field.